Determination of Employee Bonuses Using the Analytic Network Process Method at PT. Global Harvest Precision Engineering - Pratiwi; Apandi, Suliza; Veza, Okta; Majid, Sanusi; Panessai, Ismail Yusuf (Journal of Engineering, Technology, and Applied Science (JETAS), 2020)
Penelitian ini bertujuan merancang sistem pendukung keputusan dalam menentukan karyawan penerima bonus pada PT. Global Harvest Precision Engineering yang beralamat di lot 21 citra buana III Batam Centre Kepulauan Riau. Dikarenakan tidak adanya sistem pendukung keputusan yang membantu dalam menentukan karyawan penerima bonus, sehingga dibutuhkannya perancangan sistem pendukung keputusan. Data pada sistem pendukung keputusan penetuan bonus karyawan ini diperoleh dari data karyawan dari bulan januari sampai dengan Juni 2019, yang terdiri dari nama, tempat tanggal lahir, alamat dan jenis kelamin beserta data absen perbulan. Model sistem yang digunakan Data Flow Diagram (DFD). Sistem pendukung keputusan dirancang berbasis web mobile dengan menggunakan bahasa pemograman Hypertext Preprocessor (PHP) dan database MySQL. Teknik Penelitian kuantitatif, dengan mengumpulkan data-data hasil perhitungan. Penelitian menghasilkan aplikasi sistem pendukung keputusan berbasis web mobile dalam menentukan karyawan penerima bonus. Pengujian dalam aplikasi menggunakan blackbox. Determination of Employee Bonuses Using the Analytic Network Process Method at PT. Global Harvest Precision Engineering Abstract: This study aims to design a decision support system in determining employee bonus recipients at PT. Global Harvest Precision Engineering which is located at lot 21 Citra Buana III Batam Center Riau Islands. Due to the absence of a decision support system that helps in determining the bonus employee, a decision support system design is needed. Data on the decision support system for determining employee bonuses is obtained from employee data from January to June 2019, which consists of name, place of birth date, address and gender along with monthly absence data. The system model used is Data Flow Diagrams (DFD). Decision support system is designed based on mobile web using the Hypertext Preprocessor (PHP) programming language and MySQL database. Quantitative research techniques, by collecting data from calculations. The research resulted in the application of a web-based mobile decision support system in determining employee bonus recipients. In-app testing uses a blackbox. Keywords: Analytic Network Process, Decision Support System, Mobile Web.